Disentangling research on oak decline factors in Mediterranean-type climate regions: A systematic review - Marco Marques; Miguel N. Bugalho; Vanda Acácio; Filipe X. Catry (Trees, Forests and People)
The genus Quercus holds significant ecological and economic value in the Northern Hemisphere Mediterranean-type climate (MTC) regions. However, Quercus species and ecosystems are threatened by decline. Despite the importance of this genus, a comprehensive analysis of the causes of oak decline across these regions is still lacking. This study maps and analyzes research on oak decline in MTC regions, examining causal factors and Quercus species studied, while identifying knowledge gaps and future research priorities. We systematically reviewed 241 peer-reviewed articles on oak decline in MTC regions up to 2022, retrieved from the Web of Science and Scopus databases.Our findings show that scientific articles on oak decline began to be published in 1981 and peaked in 2021. Most studies focused on the Mediterranean Basin, with disparities between Northern Africa and Southern Europe. The most frequently studied species were Quercus suber L. and Quercus ilex L. in the Mediterranean Basin, and Quercus agrifolia Née and Quercus kelloggii Newb. in California, comprising 53% of all species mentioned. Pathogens (48%) and climate factors (17%) were identified as the most researched causes of oak decline. Additionally, multiple interactions between factors were identified, confirming that these combinations potentially exacerbate oak decline. Climate factors were the most frequently found in combination with others. Conversely, pathogens were mostly studied in isolation, reflecting their widely recognized role in oak decline.The study highlights the potential risk of pathogen and pest transference between MTC regions and the critical role of management practices in influencing oak decline in interaction with biotic and abiotic factors.